2008
DOI: 10.1182/blood-2008-01-135970
|View full text |Cite
|
Sign up to set email alerts
|

Syndromic thrombocytopenia and predisposition to acute myelogenous leukemia caused by constitutional microdeletions on chromosome 21q

Abstract: Several lines of evidence support the presence of dosage-sensitive genes on chromosome 21 that regulate leukemogenesis and hematopoiesis. We report a detailed clinical and molecular characterization of 3 patients with chronic thrombocytopenia caused by distinct constitutional microdeletions involving chromosomal region 21q22.12. The patients exhibited growth restriction, dysmorphic features, and developmental delays.One patient developed acute myelogenous leukemia (AML) at 6 years of age. All 3 deletions inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 22 publications
9
74
0
1
Order By: Relevance
“…The clinical features of reported cases where descriptions of hematologic findings were available are summarized in Table 2. [28][29][30][31][32][33][34][35][36] All but one case 32 reported thrombocytopenia, with qualitative platelet defects described in 2 cases. 30,36 MDS/AML developed in 3 cases, with a median age of onset of six years (range 5-8 years).…”
Section: Syndromic Cases Of Loss Of Chromosome 21q22mentioning
confidence: 99%
“…The clinical features of reported cases where descriptions of hematologic findings were available are summarized in Table 2. [28][29][30][31][32][33][34][35][36] All but one case 32 reported thrombocytopenia, with qualitative platelet defects described in 2 cases. 30,36 MDS/AML developed in 3 cases, with a median age of onset of six years (range 5-8 years).…”
Section: Syndromic Cases Of Loss Of Chromosome 21q22mentioning
confidence: 99%
“…In some FPD/ AML patients who lack CDC25C mutation, Sakurai et al identified TET2 mutation or abnormal chromosome 21 (trisomy 21) with chromosomal deletion encompassing RUNX1 locus [27]. Since both genetic events are involved in clonal expansion of HSCs and progenitors (HSPCs) [38][39][40][41], TET2 mutation or trisomy 21 could cooperate with RUNX1 haploinsufficiency to generate pre-leukemic clones. Those patients further acquired additional mutations, such as mutations in RB1, ZRSR2, and BCOR, and eventually developed overt MDS [27].…”
Section: Additional Genetic Events For Mutant Clone Expansion and Leumentioning
confidence: 99%
“…Rare cases reporting intragenic deletion of RUNX1 gene or duplication of the chromosome 21 carrying the RUNX1-deleted or mutated allele may have similar phenotype. [29][30][31] A recent study indicated that familial platelet disorder should be suspected in AML cases with a RUNX1 biallelic mutation or with a single RUNX1 mutation with a variant allele frequency more than 50%, which could indicate trisomy 21 with a duplication of the mutated chromosome or loss of heterozygosity.…”
Section: Myeloid Neoplasms With Germline Runx1 Mutationmentioning
confidence: 99%